The Effect of Sport-Related Concussion Injuries on Concussion Symptoms and Health-Related Quality of Life in Male and Female Adolescent Athletes: A Prospective Study. Issue 14 (December 2019) - McGuine, Timothy A.; Pfaller, Adam; Kliethermes, Stephanie; Schwarz, Allison; Hetzel, Scott; Hammer, Erin; Broglio, Steven
Background: Sport-related concussions (SRCs) are associated with short-term disablement, characterized as increased concussion symptoms and lower health-related quality of life (HRQoL). However, there are limited longitudinal data detailing how an SRC affects disablement beyond short-term injury recovery. Purpose: To longitudinally assess the effect of SRCs on symptoms and HRQoL in high school athletes through the 12 months after injury. Study Design: Cohort study; Level of evidence, 2. Methods: The 125 participants included high school athletes who sustained an SRC (female patients, 36%; mean ± SD age, 15.9 ± 1.1 years). The Post-concussion Symptom Scale (PCSS) from the Sport Concussion Assessment Tool–3 and the Pediatric Quality of Life Inventory 4.0 (PedsQL) were completed at enrollment and repeated at 24 to 72 hours (onset) and at 7 days (D7) after the SRC; on the date of return to play (RTP); and at 3, 6, and 12 months (M12) after the SRC. Scores at each time point were compared with the athletes' own baseline via linear mixed models for repeated measures, controlling for age, sex, and history of previous SRC and with patient as a random effect. Results: Relative to baseline, female patients reported higher PCSS symptom and severity scores at onset ( P < .001) and D7 ( P < .001), while scores were not higher ( P > .05) for RTP through M12. As compared with baseline, male patients reported higher PCSS scores at onset ( P < .001) and D7 ( P = .003) and severity scores at onset ( P < .001) and D7 ( P = .016), while the symptom and severity scores were not higher ( P > .05) at RTP through M12. Female participants reported lower PedsQL physical scores at onset ( P = .006), while scores were not lower ( P > .05) from D7 through M12. Female psychosocial scores were not lower ( P > .05) at any time after the SRC, while the total PedsQL score was lower at onset ( P = .05) but not from D7 through M12. Male physical scores were lower at onset ( P < .001) and D7 ( P = .001) but not lower ( P > .05) from RTP through M12. Male psychosocial and PedsQL scores were unchanged ( P > .05) from baseline at onset through M12. Conclusion: After an SRC, high school athletes reported initial disablement (increased symptoms and lower HRQoL) through their RTP. However, after RTP, no similar disablement was detected through 12 months after injury.